Bimbingan Konseling Islam Dalam Membentuk Kesadaran Beribadah Kepada Siswa Kolej Vokasional Nibong Tebal Malaysia - Kamal, Syauqi; Fauziah, Mira; Zalikha, Zalikha (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
Islamic counseling guidance is an effort to assist an individual or a group who are experiencing physical and emotional difficulties in fulfilling their life duties using a religious approach, namely by awakening the strength of faith to overcome problems. This study aims to investigate the religious guidance services in enhancing the worship awareness of students at Kolej Vokasional dan to analyze the obstacles that arise during the religious guidance process. The methods used in this activity are observation and interviews with Kolej Vokasional Nibong Tebal. The research findings show that there is an increased deep understdaning among students about the etiquette in the mosque, the virtues of congregational prayers, memorization of the Qunut prayer, and the pillars of prayer through religious guidance services. However, challenges such as variability in students' religious knowledge levels, limited time dan resources, and varied student responses indicate an urgent need for adaptation and improvement in program delivery. These challenges highlight the importance of differentiated teaching approaches, technology integration, and program duration extension to achieve maximum effectiveness in vocational religious education and ensure that all students can internalize the values taught most effectively dan sustainably.